2023
DOI: 10.3390/molecules28062466
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Modifications, Properties, and Practical Applications of Glass Fiber

Abstract: As a new member of the silica-derivative family, modified glass fiber (MGF) has attracted extensive attention because of its excellent properties and potential applications. Surface modification of glass fiber (GF) greatly changes its performance, resulting in a series of changes to its surface structure, wettability, electrical properties, mechanical properties, and stability. This article summarizes the latest research progress in MGF, including the different modification methods, the various properties, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 218 publications
(381 reference statements)
0
1
0
Order By: Relevance
“…Likewise, the glass platforms with thiol alkyl silane decorated with AgNPs became active for the adsorption of thiol-derivates (amino acids, drugs, dyes, etc.) [10]. Moreover, the numerous studies dealing with the functionalization of glass surfaces with organosilanes have shown that the silanization step is very sensitive and important in terms of experimental conditions and that the final surface state of the modified substrate depends strongly on temperature, the presence of water, the concentration, and the duration of the grafting step [7].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the glass platforms with thiol alkyl silane decorated with AgNPs became active for the adsorption of thiol-derivates (amino acids, drugs, dyes, etc.) [10]. Moreover, the numerous studies dealing with the functionalization of glass surfaces with organosilanes have shown that the silanization step is very sensitive and important in terms of experimental conditions and that the final surface state of the modified substrate depends strongly on temperature, the presence of water, the concentration, and the duration of the grafting step [7].…”
Section: Introductionmentioning
confidence: 99%